Information Asymmetry, Corporate Governance, and Shareholder Wealth: Evidence from Unfaithful Disclosures of Korean Listed Firms1. (October 2014) - Han, Seung Hun; Kim, Minhee; Lee, Duk Hee; Lee, Sangwon
Abstract In this study, we investigate firms that the Korea Exchange claims have made unfaithful disclosures. We find that such firms experience significantly negative stock price returns, suggesting that their managements exploit the information asymmetry involved in unfaithful disclosures to expropriate shareholder wealth. Our evidence shows that firms with higher management ownership experience a smaller decline in stock returns following notices of unfaithfulness, implying that corporate governance could improve the overall information environment and thus eventually help mitigate the information asymmetry associated with investors' lack of timely and correct information. An evaluation of idiosyncratic volatility, a direct measurement of information asymmetry, confirms our results.